POLITIK DINASTI DALAM PEMILIHAN PRESIDEN DI FILIPINA DI TAHUN 2001 â 2011 - , Etha Pasan; , Drs. Dafri Agussalim, MA, ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis focuses on analyzing the evolving political dinasties in the Philippines Presidential elections in 2001-2011. The constitution of the Philippines Chapter II Article 26 stipulates the prohibition of political dynasties, but in reality, political dynasty still occurs in presidential elections, as has happened in the year 2001-2011. Political dynasty that occurs in elections, at the congressional, legislative, and presidential, raises the pros and cons in the community. Regardless of the pros and cons, the existence of political dynasties has tarnished the democratic system adopted by the Philippine government. The election of Gloria Macapagal Arroyo and Beniqno Simeon Aquino showed inconsistencies between the rules and practices. In relation to that, this thesis asked the question "What kind of social conditions that support political dynasty that persists in the presidential election in the Philippines in the year 2001 â 2011?â. This study uses qualitative methods such as case studies and conducting a study on the factors that support the political dynasty in the presidential election by using the theories of political systems theory, patrimonial, political culture, and political clans. The results of this research study show that there are factors that contribute to political dynasties in the Philippines presidential elections in 2001 â 2011, those factors are: social class / cultural patron - client, clan politics, and parochial political culture. Social systems that exist in the society since the beginning of civilization of the Philippines, during colonization and independence, tend to form the same pattern: the formation of social class or cultural patron-client. The existence of clans increases the collaboration with parties and clan loyalty is highly strengthening the political position of the dynasties. Besides the above two factors, parochial culture still exists in Philippine society, that tends to be apathetic towards political life, makes the society vulnerable to be mobilized by the authorities. The presences of the three factors above are supported by economic circumstances, where most of the Filipinos are below the poverty line. These social conditions have contributed to the survival of political dynasty in the selection of leaders, especially in the presidential election in the Philippines.